Analisis Kemampuan Motorik Halus dan Kreativitas pada Anak Usia Dini Melalui Kegiatan Kolase - Peni Zulianti; Ayuni Yuliawati; Ela Puspitasari (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2022)
This study aims to find out how to develop children's fine motor skills through collage activities. This research is a qualitative descriptive research. Data can be collected through observation, interviews and documentation at RA At-Taqwa Jangraga. Qualitative data analysis at RA At-Taqwa Jangraga used data reduction, data presentation, and conclusion drawing. This study shows how children's fine motor skills are through collage activities such as (cutting, gluing and pasting) and how activities train children's fine motor skills (coordination of hand/finger movements, and wrists and eyes) simultaneously. Fine motor development is very important for the overall development of the child. Kindergarten-aged children still often have difficulty moving their fingers for activities such as cutting, drawing, tearing, folding, compiling and filling patterns by gluing small objects. This study aims to describe fine motor skills and creativity in early childhood through collage activities. The research method used is literature review which is carried out by collecting data or based on scientific writings that connect research with existing literature to solve a problem. Methods of collecting library data by reading and recording and managing research materials and then concluding research materials. The results of the study found that the development of fine motor skills and creativity in early childhood requires eye and hand coordination, such as composing, tearing and pasting which is done through collage activities. Based on the conclusions of this study, it is recommended that: The main objective of implementing collage activities is to improve children's fine motor skills, therefore RA/TK institutions can provide more interesting kinds of media to facilitate their students in developing fine motor skills.